Development and Validation of a Comprehensive Tool for Assessing Postgraduate Students’ Oral Presentations: Importance of the Role of Ergonomics - Mostafa, Mohammadian; Vahid, Gharibi; Hayat, Ali Asghar; Cousins, Rosanna; Mokarami, Hamidreza (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The aim of this exploratory sequential mixed methods study was to develop an oral presentations assessment tool for postgraduate students’ oral presentations. Methods: First, a literature review and the ideas of 319 experienced professors were used to identify domains and potential items to develop the desired tool. Then the psychometric properties of the preliminary tool were measured using face and content validity, inter-rater agreement and test-retest reliability. Results: The qualitative phase indicated there should be four domains in the developed Oral Presentations Assessment Tool: subject knowledge, delivery, content and organization, and ergonomics, and that items in the developed tool should be weighted according to importance for the efficacy of a presentation. The final version included 19 items across four domains. Mean content validity index and content validity ratio scores were 0.93 and 0.76, respectively. Spearman’s rank correlation coefficient for the two evaluation periods was 0.92. The intra-class correlation coefficient was 0.78. Conclusion: The Oral Presentations Assessment Tool has appropriate psychometric properties and can be used as a valid and applicable instrument to assess postgraduate students’ oral presentations. Important cognitive factors in oral presentations in the form of an ergonomic domain was included for the first time, as part of this new comprehensive tool.